2007
DOI: 10.1128/jvi.00180-07
|View full text |Cite
|
Sign up to set email alerts
|

Natural Recombination Event within the Capsid Genomic Region Leading to a Chimeric Strain of Human Enterovirus B

Abstract: Recombination between two strains is a known phenomenon for enteroviruses replicating within a single cell. We describe a recombinant strain recovered from human stools, typed as coxsackievirus B4 (CV-B4) and CV-B3 after partial sequencing of the VP1 and VP2 coding regions, respectively. The strain was neutralized by a polyclonal CV-B3-specific antiserum but not by a CV-B4-specific antiserum. The nucleotide sequence analysis of the whole structural genomic region showed the occurrence of a recombination event … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 37 publications
0
21
0
1
Order By: Relevance
“…Alternatively, these discrepancies may have resulted from recombination events that had occurred within the capsid region. Such events are believed to be infrequent, probably because of the structural constraints imposed on virions, but previous studies have shown that they can occur in both PV species (14,15,23,36,39,60,67) and non-PV HEV species (16). Further analyses are under way to determine whether the discrepancies observed between the VP1 and VP2 methods for some samples can be attributed to such uncommon recombination events.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, these discrepancies may have resulted from recombination events that had occurred within the capsid region. Such events are believed to be infrequent, probably because of the structural constraints imposed on virions, but previous studies have shown that they can occur in both PV species (14,15,23,36,39,60,67) and non-PV HEV species (16). Further analyses are under way to determine whether the discrepancies observed between the VP1 and VP2 methods for some samples can be attributed to such uncommon recombination events.…”
Section: Discussionmentioning
confidence: 99%
“…Enteroviral evolution occurs through genetic drift (Chua et al, 2001), which is primarily prominent in group B enteroviruses (Simmonds & Welch, 2006), including coxsackieviruses of group B (CVB). In addition, the occurrence of interserotypic recombination events between different coxsackievirus strains has also been reported (Bouslama et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In the region 2A, LR51A5, and LR61G3 cluster with the CBV6 prototype strain (82% nucleotide identity), and in 2B with the EV82 prototype strain (84% nucleotide identity). In the region 2C-3D there is a continuous phylogenetic relationship of LR51A5 and LR61G3 with E30 strains E30-CF1319-02, E30-CF1500801-05, and E30-CF1590401 isolated in France in 2002-2005, as well as with strain SE-03-78616, belonging to CBV4, isolated in France in 2003 and found to be recombinant in the 2A genomic region with the above-mentioned E30 isolate E30-CF1319-02 [17]. The nucleotide identity between LR51A5 and LR61G3 and the E30 ''sequences'' was 83-84% in 2C, 84-86% in 3A, 87-92% in 3B, 89-91% in 3C, and 88-89% in 3D.…”
Section: Resultsmentioning
confidence: 94%
“…Recombination has been recognized as a frequent event in Poliovirus [6][7][8][9][10][11] and non-polio Enterovirus evolution [12][13][14][15][16], usually located in the noncapsid coding region. Intra-and interserotypic recombination events in the VP2-VP1 coding region have been reported to occur rarely [6,17,18]. Genetic exchanges between enteroviruses can give rise to new viral genotypes that may be extremely virulent and dangerous for public health [19].…”
Section: Introductionmentioning
confidence: 99%